Molecularly imprinted polymeric coatings for sensitive and selective gravimetric detection of artemether. Issue 57 (16th September 2020) - Arshad, Usman; Mujahid, Adnan; Lieberzeit, Peter; Afzal, Adeel; Bajwa, Sadia Zafar; Iqbal, Naseer; Roshan, Sumaira
Abstract : Chemical structures of the antimalarial drugs: artemisinin, artemether (a methyl ether derivative of artemisinin), and lumefantrine. Abstract : Monitoring antimalarial drugs is necessary for clinical assays, human health, and routine quality control practices in pharmaceutical industries. Herein, we present the development of sensor coatings based on molecularly imprinted polymers (MIPs) combined with quartz crystal microbalance (QCM) for sensitive and selective gravimetric detection of an antimalarial drug: artemether. The MIP coatings are synthesized by using artemether as the template in a poly(methacrylic acid- co -ethylene glycol dimethacrylate) matrix. Artemether-MIP and the non-imprinted polymer (NIP) control or reference layers are deposited on 10 MHz dual-electrode QCM by spin coating (187 ± 9 nm layer thickness after optimization). The coatings are characterized by FTIR spectroscopy and atomic force microscopy that reveal marked differences among the MIP and NIP. The MIP-QCM sensor exhibits high sensitivity (0.51 Hz ppm −1 ) with sub-10 ppm detection and quantification limits. The MIP-QCM sensor also exhibits a 6-fold higher sensitivity compared to the NIP-QCM, and a dynamic working range of 30–100 ppm. The response time of MIP-QCM devices for a single cycle of analyte adsorption, signal saturation, and MIP regeneration is less than 2.5 min. The sensor also demonstrates selectivity factors of artemether-MIP of 2.2 and 4.1 compared to artemisinin and lumefantrine, respectively. Reversibility tests reveal less than 5% variation in sensor responses over three cycles of measurements at each tested concentration. The MIP-QCM showed lower detection limits than conventional HPLC-UV, and faster response time compared to HPLC-UV and liquid chromatography-mass spectrometry (LC-MS).